Risk [videorecording (DVD)] - Assange, Julian; Lady Gaga (Virgil Films, 2017)
Laura Poitras returns with her most personal and intimate film to date. Filmed over six years, the film is a complex and volatile character study that collides with a high-stakes election year and its controversial aftermath.